MEDIATION AND ECOLOGICAL SUITABILITY OF DIDACTIC-MATHEMATICAL AND TECHNOLOGICAL KNOWLEDGE OF TEACHERS IN THE MATHEMATICS EDUCATION PROGRAM AT THE UNIVERSIDAD DE COSTA RICA - Vargas Gamboa, José David (2025)
The purpose of this article is to communicate the analysis of the mediational and ecological facets of didactic-mathematical knowledge among faculty members in the Mathematics Education program at the Universidad de Costa Rica (UCR). This analysis was conducted by the author as part of their master's research. The study employed a qualitative descriptive approach, examining these facets and exploring the various ways digital resources and technological tools are utilized. One of the key findings is the significant potential for improvement in integrating technology into the educational process, particularly in areas related to resource design and communication. Future research within the same population is recommended to explore additional dimensions of didactic-mathematical knowledge, providing a more comprehensive understanding of faculty characteristics.